Deciphering the Effects and Mechanisms of Yi-Fei-San-Jie-pill on Non-Small Cell Lung Cancer With Integrating Network Target Analysis and Experimental Validation - Yang, Hongxing; Guo, Qiuyan; Wu, Jianbin; Zhong, Lixia; Sun, Lingling; Liu, Wei; Wang, Jigang; Lin, Lizhu (Frontiers in Pharmacology, 2022)
Non-Small Cell Lung Cancer (NSCLC), which accounts for 85% of lung cancer, calls for better therapy. Yi-Fei-San-Jie-Pill, a well applicated traditional Chinese medicine formula, was reported to be effective in the treatment of NSCLC. Whereas, it’s anti-tumor mechanism still need to be fully elucidated. Herein, a reliable preclinical orthotopic but not subcutaneous model of NSCLC in mice was established to evaluate the anti-cancer characters and further validate the mechanisms of Yi-Fei-San-Jie-Pill. Bioinformatic analysis was executed to identify the potential targets and key pathways of Yi-Fei-San-Jie-Pill on NSCLC. In detail, the anti-tumor effect of Yi-Fei-San-Jie-Pill and the autophagy inhibitor 3-MA was evaluated according to the tumor fluorescence value and comparation of different groups’ survival time. As a result, Yi-Fei-San-Jie-Pill, markedly decreased tumor size and prolonged survival time in contrast with those in model group (P<0.05), also regulated the protein expression levels of apoptosis- and autophagy-related proteins dramatically. In conclusion, this study provides convincing evidence that Yi-Fei-San-Jie-Pill could inhibit the growth of tumor and prolong the survival time of tumor-bearing mice based on NSCLC orthotopic model and its anti-tumor effect was closely associated with the promotion of apoptosis and interfering of autophagy coupled with regulation of immune infiltration.